Sự giải hấp thuốc trừ sâu từ đất ruộng bị ngập - Hà, Trịnh Thu; W. Strowble, Bjarne; Trung, Nguyễn Quang; Giang, Lê Trường (Vietnam Journal of Chemistry, 2016)
The use of agriculture chemicals is one of the factors causing pollution of ground - and surface water by its dispersion into the environment. Desorption of fenobucarb, endosulfan, dichlorodiphenyltrichloroethane (DDT) from insecticides spiked rice soil column to flooding water were studied under oxidized and reduced condition combining with factors like insecticides initial concentration, dissolve organic carbon (DOC) content in flooding water and flooding time. Desoptions of fenobucarb, endosulfan and DDT from soil to flooding water ratio with initial of pesticides in soil were studied. Added DOC in flooding under oxidized conditions enhanced more DDT, endosulfan and fenobucarb desorption than under reduced condition. Keywords. Pesticides, rice soil, flooding water, disolve organic carbon